Impact of smartphones on students: How age at first use and duration of usage affect learning and academic progress. (August 2022) - Han, Sunyoung
Abstract: This study examined how smartphones affect students in current times where they are gradually penetrating into our lives. This study used data from the Seoul Educational Longitudinal Study, of which the 9th year panel data was used. Structural equation modeling was utilized to examine the impacts of the age of the students when they use smartphones for the first time and how long they use it once addicted. The self-directed learning ability and academic achievement scores were also examined. It was found that the age at which the students started using smartphones affected their daily smartphone usage hours and their degree of smartphone addiction. Moreover, the amount of time the students used smartphones for entertainment or learning had different effects on smartphone addiction and self-directed learning ability directly and indirectly on academic achievement in Korean, mathematics, and English. The implications on education and research are also discussed. Highlights: The age at first smartphone use affected the smartphone usage and smartphone addiction. The smartphone use for entertainment had different effects on smartphone addiction and self-directed learning ability. Smartphone addiction was found to have different effects depending on the subject.